Early working memory is a significant predictor of verbal and processing skills at 6–7 years in children born extremely preterm. (August 2020) - Lowe, Jean; Bann, Carla M.; Fuller, Janell; Vohr, Betty R.; Hintz, Susan R.; Das, Abhik; Higgins, Rosemary D.; Watterberg, Kristi L.; ,
Abstract: Objective: The study was designed to investigate whether attainment of object permanence, a measure of early working memory used at 18–22 months corrected age, was associated with executive function at 6–7 years in a cohort of children born extremely preterm. Study design: Children enrolled in the Neuroimaging and Neurodevelopmental Outcome (NEURO) study, a secondary study to the Surfactant Positive Airway Pressure and Pulse Oximetry Trial (SUPPORT) of the NICHD NRN, were eligible for this longitudinal study. Testing completed at 18 to 22 months corrected age was compared to testing at school age with a specific focus on measures of executive function. Results: Children who had achieved object permanence mastery at a corrected age of 18–22 months had higher mean scores on the WISC-IV tests of verbal comprehension and processing speed at age 6–7 years. Regression models indicated that object permanence scores were significant predictors of both verbal comprehension and processing speeds scores, after controlling for other factors. When analyzed by subgroup for sex, these results were significant for girls but not for boys. Conclusions: This study found that an early mastery of object permanence was associated with higher scores in areas of verbal comprehension and processing speed in girls. These results have implications for potentially identifying young children born preterm that are at greater risk for difficulties with cognitive and working memory skills at school age. Highlights: Object permanence at 18 months was associated with testing of preterm 7-year olds. Object permanence score was associated with cerebellar lesions on MRI at birth. Object permanence score was associated with WISC-IV verbal comprehension score. Object permanence was associated with working memory scores in girls born preterm.